2015
DOI: 10.1007/s00707-015-1373-8
|View full text |Cite
|
Sign up to set email alerts
|

Electromechanical responses of piezoelectric nanoplates with flexoelectricity

Abstract: Flexoelectricity, representing the coupling between electrical polarizations and strain gradients, should be taken into account in the analysis of electromechanical responses of nanostructures where large strain gradients are expected. In this paper, we will explore the influence of flexoelectricity on the electromechanical coupling behavior of a simply supported piezoelectric nanoplate by using the Kirchhoff plate theory. The governing equations and corresponding boundary conditions are deduced from Hamilton'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(31 citation statements)
references
References 31 publications
5
26
0
Order By: Relevance
“…In Reference [ 74 ], the flexoelectricity was found to increase the deflection while decreasing the resonant frequency of the plate. However, for the case presented in Reference [ 98 ], opposite trends of the flexoelectricity on the plate deflection and resonant frequency were observed. Recently, Liang et al [ 99 ] studied the buckling and vibration of a piezoelectric nanofilm and found that the critical buckling load and the natural frequency of the film with the consideration of the flexoelectricity are higher than those obtained by the classical piezoelectricity plate theory.…”
Section: Size-dependent Properties Of Pnsmentioning
confidence: 89%
See 1 more Smart Citation
“…In Reference [ 74 ], the flexoelectricity was found to increase the deflection while decreasing the resonant frequency of the plate. However, for the case presented in Reference [ 98 ], opposite trends of the flexoelectricity on the plate deflection and resonant frequency were observed. Recently, Liang et al [ 99 ] studied the buckling and vibration of a piezoelectric nanofilm and found that the critical buckling load and the natural frequency of the film with the consideration of the flexoelectricity are higher than those obtained by the classical piezoelectricity plate theory.…”
Section: Size-dependent Properties Of Pnsmentioning
confidence: 89%
“…The vibration analysis of a simply supported piezoelectric nanobeam revealed that the flexoelectricity tends to reduce its resonant frequency [ 73 ]. The size-dependent bending and vibration characteristics of a clamped and a simply supported nanoplate were studied by Zhang et al [ 74 ] and Yang et al [ 98 ], respectively, based on the Kirchhoff plate model. In Reference [ 74 ], the flexoelectricity was found to increase the deflection while decreasing the resonant frequency of the plate.…”
Section: Size-dependent Properties Of Pnsmentioning
confidence: 99%
“…Table 4. Material properties of the visco-piezo-flexoelectric nanobeam [36,39,71]. In choosing a value for the nonlocal parameter, we used 0.5 nm < e 0 a < 0.8 nm [72] and 0 < e 0 a ≤ 2 nm [73,74], and on the other side, the SGLP could be chosen arbitrarily.…”
Section: Frequency Analysismentioning
confidence: 99%
“…Laboratory tests are limited in measuring, explaining and quantifying the key flexoelectric phenomena at specific conditions [Catalan, Lubk, Vlooswijk et al (2011); Baskaran, He, Chen et al (2011); Bhaskar, Banerjee, Abdollahi et al (2016)]. Besides, further theoretical basis studies have been presented to investigate the flexoelectric phenomena in various structures under different configurations [Sharma, Maranganti and Sharma (2007); Mao and Purohit (2015); Yang, Liang and Shen (2015)]. However, relatively few numerical works have been documented to simulate flexoelectricity.…”
Section: Introductionmentioning
confidence: 99%